Spontaneous clarity - a new reality dawns: Psychotherapists’ lived experience of epiphany moments - McGovern, Melanie (European Journal for Qualitative Research in Psychotherapy, 2021)
This article presents findings from the author’s doctoral research into psychotherapists’ perceptions of their moments of self-awareness and epiphanies. Following a review of existing research on this phenomenon, the author used a reflexive, hermeneutic phenomenological approach to analyze textual data, including interview transcripts, generated by seven experienced psychotherapists. The author also drew on a written account of her own experience of the phenomenon in order to strengthen the transparency of the study and aid interpretation. Data analysis suggested that, for therapists, manifested moments of self-awareness encompassed four existential dimensions: spatiality, corporeality, temporality and relationality. Five major themes emerged: ‘Spontaneous clarity - A new reality dawns’; ‘Cross the conscious threshold - Makes the truth much bigger’; ‘Inner knowingness manifests’; ‘Tipping point’; and ‘Vacillation’. This research adds to existing literature in highlighting this phenomenon with a greater breadth and depth of clarity. Hermeneutic phenomenology encouraged a nuanced understanding of an epiphany with the sense of crossing a threshold into a conscious space. In addition, the high degree of body connectedness therapists experienced in such moments and how it displayed its own idiosyncratic sense of time added further knowledge on this topic. The idea of oscillating awareness, where the therapists experience a flux between the cultivation of consciousness and retreating from awareness, supplements the current literature.